Determinants of Regional University Development in Modern Russia - Bachiev, Bachey A.; Markaryan, Julia A.; Pashtaev, Bulat D.; Savina, Veronika I.; Smyshnov, Konstantin M.; Feyzullayev, Fyodor S.; Kharchenko, Leonid N. (Journal of History Culture and Art Research, 2017)
The article describes the determinants that are manifested in regional social-economic complexes and determine the main trends of development and educational activities for regional universities. The authors determined and characterized such determinants as social-economic (or financial, and infrastructural) uneven development of Russia; the economic mechanism of higher education economic accessibility stratification; the need to equalize the professional educational network in the regions of Russia to ensure the development of the intellectual and professional potential of regions and the gradual equalization of Russia economic development in terms of regional and geographical dimensions; the degree of "openness-closure" concerning a regional university and the development of understanding that a university is a system by its structural and functional organization and, consequently, the subject to the laws of social, ethnic, state and regional morphology of education; an ambiguous (often negative or neutral) attitude of teachers and organizers of higher education to innovations, which creates the contradictions and extends the periods of crisis processes in the educational system of a regional university.